Upaya Membangun Sustainable Tourism Bermuatan Ideologi Pancasila di Eduwisata Ndalem Kerto Ponorogo - Marsudi, Kenlies Era Rosalina; Purbasari, Verbena Ayuningsih (Journal of Civic Education, 2025)
The post-pandemic era has increased global awareness of sustainability, particularly in the tourism sector, where responsible practices are now essential. Pancasila serves as a guiding framework for sustainable tourism, promoting diversity, cooperation, and unity while fostering an inclusive and culturally respectful environment. This study employs a qualitative field research approach at Eduwisata Ndalem Kerto Ponorogo, an educational tourism site integrating plantation and livestock farming. The site emphasizes environmental conservation, cultural heritage, and community empowerment through Pancasila-based sustainability principles, including nature conservation, community engagement, cultural diversity management, deliberative decision-making, and economic equity. Findings reveal that integrating Pancasila’s values strengthens environmental conservation, socio-cultural resilience, and economic inclusivity. The Eduwisata model offers a replicable framework for other Indonesian tourism destinations, illustrating how local wisdom and national ideology can shape responsible and sustainable tourism development.